A comprehensive study on green roof performance for retrofitting existing buildings. (15th May 2018) - Cascone, Stefano; Catania, Federico; Gagliano, Antonio; Sciuto, Gaetano
Abstract: Green roofs present a viable solution for increasing rainwater retention while improving the energy performance of both new and existing buildings. Considering the widespread occurrence of existing buildings, it is worthwhile to conduct an in-depth analysis of green roof feasibility for retrofitting these buildings. In such cases, the first constraint is related to structural compatibility. Therefore, the use of lightweight systems should be prioritized to minimize overloading of the existing roof. Another possible constraint concerns the viability of green roofs. The main advantages of green roofs are their energy savings and environmental benefits. In this study, different green roof solutions were evaluated and their performance was compared against the findings of previous studies. The analysis was carried out in the Mediterranean city of Catania, and the results show that only green roof solutions with a load limit of 1.46 kN/m 2 are suitable for retrofitting existing buildings. As regards the energy savings, energy consumption for cooling was reduced by 31–35%, and during winter, energy consumption for heating decreased by 2–10%. The environmental benefits were quantified during summer and compared to those of non-vegetated roofs. The results show removals of 1.35 kg m -2 ·y −1 of CO2 and 0.03 kg m -2 ·y −1 of NO2 . Finally, the economic analysis indicates that the discounted payback time of the investment varies from 13 to 18 years depending on the substrates and vegetation used on the green roof. Highlights: Overloading of older building structures with new green roofs was evaluated. Densities of dry and water-saturated substrates were compared. Only some green roof package may be implemented on existing building. Payback time of the investment varies between 13 and 18 years. Retrofitting reduces CO2 emissions in the atmosphere by about 1.41 kg/m 2 .